2019
DOI: 10.1039/c8cp07542e
|View full text |Cite
|
Sign up to set email alerts
|

Cations brought together by hydrogen bonds: the protonated pyridine–boronic acid dimer explained

Abstract: Stable dimers of protonated pyridine–boronic acid are found in the gas phase and solvent models. The importance of electrostatics is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 43 publications
(47 reference statements)
7
36
0
Order By: Relevance
“…The catalogue of metastable H‐bonded complexes of like charged ions was expanded to dications and dianions. Anion‐anion H‐bonding has recently been identified within a crystal structure, with computational confirmation, and analysis of the CSD identified protonated pyridine‐boronic acid dimers in the solid phase. Computational tools verified that a metastable complex is converted to a global minimum within a dielectric.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The catalogue of metastable H‐bonded complexes of like charged ions was expanded to dications and dianions. Anion‐anion H‐bonding has recently been identified within a crystal structure, with computational confirmation, and analysis of the CSD identified protonated pyridine‐boronic acid dimers in the solid phase. Computational tools verified that a metastable complex is converted to a global minimum within a dielectric.…”
Section: Discussionmentioning
confidence: 91%
“…Considering this background, it was quite surprising when a number of reports appeared asserting that a H‐bond could be present between a pair of species of like charge . One would have presumed that the Coulombic repulsion ought to prevent the two ions from approaching one another.…”
Section: Introductionmentioning
confidence: 99%
“…The anion‐anion repulsion imposes a large energetic barrier of around 160–180 kJ/mol which must overcome so that the complexes can be formed . This large energetic barrier has been observed in other anion‐anion interactions . The joint analysis of electrostatic potential and electron density topologies performed on neutral and charged complexes derivatives of oxoacids revealed that the stability of the complexes in the gas phase is explained by attractive forces localized in a volume situated in the HB and defined as the electrostatic attraction region .…”
Section: Introductionmentioning
confidence: 97%
“…[37][38][39] The latter interaction was named as antielectrostatic interaction [40] and it was a subject of controversies and debates. [41][42][43][44] However these systems in spite they correspond to energetic minima they are characterized by positive binding energies. [44] The complexes considered here correspond to energetic minima; and additionally both {F 11 } À H + + {Y} + !…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43][44] However these systems in spite they correspond to energetic minima they are characterized by positive binding energies. [44] The complexes considered here correspond to energetic minima; and additionally both {F 11 } À H + + {Y} + ! {F 11 } À ···H + ···{Y} + and {F 11 } À + H + {Y} + !…”
Section: Discussionmentioning
confidence: 99%